Intelligent monitoring system of unburned carbon of fly ash for coal fired power plant boiler - Gurusingam P.; Basim Ismail F.; Gunnasegaran P.; Sundaram T. (EDP Sciences, 2023)
Coal; Coal ash; Coal combustion; Coal fueled furnaces; Fly ash; Forecasting; Monitoring; Neural networks; Artificial neural network modeling; Coal fired plants; Coal-fired power plant; Conventional methods; Electricity demands; Incomplete combustion; Intelligent monitoring systems; Unburned carbon in fly ashes; Fossil fuel power plants